PENGARUH PELATIHAN PLAIOMETRIK DOUBLE LEG BOUND TERHADAP PENINGKATAN POWER OTOT TUNGKAI - Kharisma, N. Riang (Jurnal Ilmu Keolahragaan Undiksha, 2013)
The research aimed to determine the effect of training plaiometrick double leg bound to increase leg muscle power. This research is a quasi experimental research (quasi-experimental) with the design of the Modified Control Group Pretest Posttest Design. The study population was a student of class VII student son football extracurricular participants SMP N 3 Singaraja school year 2012/2013, amounting to 96 people. The subjects of the training plaiometrick double leg bound numbered 96 people. Limb muscle power was measured with a standing broad jump test, then the data were analyzed by independent t-test at significance level (α) of 0.05 with SPSS 16.0. Based on the results of independent t-test results obtained for variable leg muscle power, the results of the treatment group and the gaint score control group obtained the value thitung = 11.391 with a significance value of 0.000. Calculated significance value smaller than the value of α (Sig <0.05), thus the research hypothesis "plaiometrick double leg bound training effect on leg muscle power" acceptable. From the results of this study concluded that plaiometrick double leg bound training effect on limb muscle power class VII student son football extracurricular participants SMP N 3 Singaraja school year 2012/2013. Recommended for sports people (coaches, trainers, athletes and gym teacher) to use the plaiometrick double leg bound training as an alternative to improve leg muscle power.